1995
DOI: 10.1099/0022-1317-76-3-661
|View full text |Cite
|
Sign up to set email alerts
|

Human foamy virus infection activates class I major histocompatibility complex antigen expression

Abstract: We examined the effect of human foamy virus (HFV) infection on the expression of human major histocompatibility complex molecules. Our data show that in vitro HFV infection of U373-MG glioblastoma cells results in increased expression of class I human leukocyte antigen (HLA) and transcripts. Transient transfection assays of plasmids containing the reporter gene chloramphenicol acetyl transferase driven by different 5' deletions of the HLA-All class ! promoter allowed identification of eis-acting elements invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…In particular, the interaction of FV with the human immune system remains poorly characterized. It has been suggested that FV does not activate an innate response (10,62). Previous experiments were performed mostly with human or simian epithelial cell lines, and the response of human hematopoietic cells to the virus is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the interaction of FV with the human immune system remains poorly characterized. It has been suggested that FV does not activate an innate response (10,62). Previous experiments were performed mostly with human or simian epithelial cell lines, and the response of human hematopoietic cells to the virus is not known.…”
Section: Discussionmentioning
confidence: 99%
“…Very little is known about the sensing of FV. A few reports, published almost 2 decades ago, described an absence of type I IFN production by human and primate cell lines (such as U373-MG glioblastoma cells and AV3 embryonic amniotic cells) upon FV infection (10,60,62). However, how pDCs and other hematopoietic cells react when they encounter FV has not been investigated thus far.…”
mentioning
confidence: 99%
“…Innate immune system sensing of FV infections is poorly characterized. A failure of FVs to induce type I interferon (IFN-I) was suggested by early studies using primate or human cell lines [73,74,75]. A very recent study by Rua and colleagues, however, demonstrates that FVs are efficiently sensed by primary human hematopoietic cells [76].…”
Section: Innate Sensing and Cellular Restriction Factors Of Fvsmentioning
confidence: 99%
“…Our results underline the importance of extending current knowledge beyond the most studied prototype strain. Indeed, Tas interacts with promoters from host genes (Colas et al, 1995;Kido et al, 2002;Wagner et al, 2000;Wang et al, 2010), may be involved in clinically relevant interactions with lentiviruses (Choudhary et al, 2013), and is a potential (but still controversial) target of the immune system (Meiering and Linial, 2003;Regad et al, 2001).…”
Section: Resultsmentioning
confidence: 99%